Mapping the TQM implementation: An empirical investigation of the cultural dimensions with different strategic orientation in Indian firms. Issue 8 (29th November 2018) - Kumar, Vimal; Sharma, R.R.K.; Verma, Pratima; Lai, Kuei-Kuei; Chang, Yu-Hsin
Abstract : Purpose: Culture is considered as one of the variables that influence the total quality management (TQM) adoption process. The purpose of this paper is to explore the relationship between cultural dimensions and the strategy of the firms in TQM implementation. These relationships are the subject of prior research. Furthermore, the authors make a comparative analysis of cultural dimensions on strategic choices of the firms, i.e. innovators, prospectors and defenders in TQM implementation. Design/methodology/approach: From the existing literature review on TQM practices and organizational culture, 14 cultural dimensions were employed with organizational strategy in this present study. By using survey data collection method, 111 Indian firms were selected. The authors considered three strategy parameters and six structural attributes to identify the strategy of the firms, namely innovators, prospectors and defenders identified using cluster analysis. Furthermore, the relationship between organizational culture and strategy was examined using one-way ANOVA approach. Findings: The results of the study revealed that eleven of the fourteen hypotheses supported which relating the cultural dimensions to TQM implementation with the strategic orientation. With the help of significant related values of cultural dimensions to the particular strategic firms, it is also found that implementation of TQM is easy or not. Some of the organizations with a particular strategic orientation will be able to implement TQM easily and successfully but some organizations will have difficulty to implement it successfully. Practical implications: The firms hold their importance with respect to the different strategic orientation toward the various aspects of organizational cultures and TQM approaches in its implementation. Managerially, due to increased business competitiveness and economic pressures, top management sees the way in adopting TQM practices to achieve a competitive advantage. Apparently, it is evident that matching of TQM practices for a different strategy of the firms with various cultural dimensions leads to the smooth functioning of the organization. This study helps to the current organizations in implementing TQM with their respective culture. Originality/value: This research can be useful for three strategic firms, namely innovators, prospectors and defenders to achieve effective implementation of TQM practices with consideration and understanding of the advantage of each culture dimension. The framework of the current study represents the effectiveness in assessing the TQM practices in individual cultural dimensions and its significant role.